Design of service quality and analysis of customer satisfaction in SME culinary products with the quality function deployment method - Supriyati, Supriyati; Putra, Fibi Eko; Widya, Adi Rusdi (Operations Excellence: Journal of Applied Industrial Engineering, 2023)
SMEs are medium-level community businesses with limited capital. The type of business that can revive the economy, especially the economy for families, is the SMEs culinary business which is consumed by the community every day. One of the SMEs that is still surviving despite experiencing a decline is the SMEs in the culinary field. The results of observations and interviews with one of the SMEs culinary businesses, in a period of 12 months, sales decreased by an average of up to 50%. The cause of the decline in sales is not known with certainty, so it is necessary to evaluate the performance of these SMEs. QFD is one method that can be used to obtain a clear and objective picture of Customer needs. The research method involves Customers as respondents, the number of samples is 80 with 26 valid and reliable attributes. The results of the analysis using Importance Performance Analysis (IPA) show that there are five attributes that are considered important for Customers to become priority improvements. These attributes are related to the Tangible aspect, namely the presentation of Durian sticky rice products that are attractive, the portion according to expectations, Assurance, namely the consistency of the ripeness of the durian fruit, the taste of the durian fruit is felt in every portion, Empathy, namely the ethics in serving Customers. Based on the QFD approach, the priority is the technical importance rating by making standard operating procedures for each technical response in the form of standard operating procedures for checking raw materials and the amount of raw materials used in each serving, re-examining, providing the composition of the main raw materials so that the taste remains consistent (Assurance). Serving techniques with serving portions, cleanliness of physical facilities (Tangible), service to Customers and socialization of Customer service standards (Emphaty), and ordering techniques (reliability). So that in order to maintain and maintain the quality of SMEs products and services in the culinary field, it is necessary to conduct a performance assessment, especially related to the four aspects of service quality Assurance, Tangible, Empathy and Reliability as a design in assessing service quality